2011
DOI: 10.5367/te.2011.0048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Agritourism Activity in Italy: Facility Based or Local Culture Based?

Abstract: This paper identifies which diversified activities influence the price level of agritourism and how they do so. A hypothesis that contrasts two types of activity (facility based and local culture based) is examined. First, from a conceptual perspective, the authors note that agritourism based on local cultural resources can internalize positive externalities, which are uniquely nurtured local cultural resources, into income – unlike facility based activity that has no connection with local cultural resources. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 20 publications
4
37
0
2
Order By: Relevance
“…Overall, the paper provides some homogenous findings with previous studies (Galluzzo, 2015;Ohe & Ciani, 2011;Santeramo, 2015) and, at the same time, offers an integrated demand-supply framework that can be implemented in other studies and in other economic sectors. As a limitation, the empirical data can be regarded as rather narrow.…”
Section: Probabilistic Modelingsupporting
confidence: 66%
“…Overall, the paper provides some homogenous findings with previous studies (Galluzzo, 2015;Ohe & Ciani, 2011;Santeramo, 2015) and, at the same time, offers an integrated demand-supply framework that can be implemented in other studies and in other economic sectors. As a limitation, the empirical data can be regarded as rather narrow.…”
Section: Probabilistic Modelingsupporting
confidence: 66%
“…Existing agritourism studies predominantly focus on the characteristics of the supply, either profiling the product offered (e.g., types of activities, seasonality) orexamining the entrepreneurial motivations and levels of satisfaction of their providers (Barbieri & Mahoney, 2009;McGehee& Kim, 2004;Ollenburg& Buckley, 2007;Tew& Barbieri, 2013).Although a growing number of studies on the demand for agritourism is gaining space in the international scientific platform (e.g., Carpioet al, 2008;Ohe & Ciani, 2011;, such information is scatter. The scant and disperse literature on agritourism demand, coupled with a steady growth in its supply andan increasing interest in promoting this alternative form of tourism (Gil Arroyo et al, 2013), calls for the integration of the existing information to shed light on future research directions.…”
Section: Introductionmentioning
confidence: 99%
“…One strand of literature addresses the demand of agritourism (Busby and Rendle ; Carpio et al . ; Ohe and Ciani ; Santeramo ; Santeramo and Barbieri ). These studies found that farms in rural areas were receptive of consumer demand for agritourism.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Agritourism has taken root in the United States (Khanal and Mishra ; Sotomayor et al . ), Italy (Ohe and Ciani ), the United Kingdom (Ilbery et al . ; Bernardo et al .…”
Section: Introductionmentioning
confidence: 99%